The Role of School Members in Organizational Culture for Work Skills’ Formation : Responding to Era of The Industrial Revolution 4.0 Challenges - Asmawan, Moh. Chairil; Ulfatin, Nurul; Wiyono, Bambang Budi; Burhanuddin, Burhanuddin (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
The research aims to reveal school membersâ€™ role in the organizational culture development in increasing skills in Vocational High Schools. The study method used was ethnographic with a qualitative approach. Data collection employed interviews and observations. Interviews were conducted with principals, teachers, students, and studentsâ€™ parents in Vocational High Schools in Sukoharjo Regency, Central Java Province, Indonesia. Data analysis used interactive analysis, and its validity was checked by triangulation. The results showed that the principal’s role in developing organizational culture was to establish organizational culture through the school’s vision and mission, develop work programs, and establish school regulations. Provide guidance to school residents in two ways: structurally and non-structurally. Delegating tasks and authorities according to the expertise of each teacher and staff. Provide assessments and rewards and carry out coordination and supervision. At the same time, the role of the teacher is to continue and develop the values of life. Train to develop skills in students. In addition, the role of parents or families in children’s education clearly affects the personality of children or students. The family environment was the first and main medium that directly or indirectly influenced behavior in student development.